2016
DOI: 10.1128/microbiolspec.mchd-0050-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cell-Autonomous Effector Mechanisms in Macrophages versus Non-Immune Cells

Abstract: Summary Specialized adaptations for killing microbes is synonymous with phagocytic cells including macrophages, monocytes, inflammatory neutrophils and eosinophils. Recent genome sequencing of extant species, however, reveals analogous antimicrobial machineries exist in certain non-immune cells and also within species that ostensibly lack a well-defined immune system. Here we probe the evolutionary record for clues about the ancient and diverse phylogenetic origins of macrophage killing mechanisms and how some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 228 publications
1
11
0
Order By: Relevance
“…1). Hence the birth of GBPs predates IFN signaling, with their primordial defense functions being refashioned in early gnathostomes (jawed vertebrates) to respond to cytokine stimulation (Kim et al, 2012; Gaudet et al, 2016; Secombes and Zou, 2017). Despite differences in inducibility, a consistent feature across most species is the expansion of GBPs into chromosomally clustered multigene families that include as many as 16 paralogues in Paramecium tetraurelia (Li et al, 2009; Shenoy et al, 2012; Fig.…”
Section: Gbps In Humans and Other Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Hence the birth of GBPs predates IFN signaling, with their primordial defense functions being refashioned in early gnathostomes (jawed vertebrates) to respond to cytokine stimulation (Kim et al, 2012; Gaudet et al, 2016; Secombes and Zou, 2017). Despite differences in inducibility, a consistent feature across most species is the expansion of GBPs into chromosomally clustered multigene families that include as many as 16 paralogues in Paramecium tetraurelia (Li et al, 2009; Shenoy et al, 2012; Fig.…”
Section: Gbps In Humans and Other Vertebratesmentioning
confidence: 99%
“…5 B). Such partners often reflect the antimicrobial machinery expressed in immune versus nonimmune cells (Gaudet et al, 2016). For example, in IFN-γ–activated mononuclear phagocytes, certain GBPs interact with the phagocyte oxidase complex (phox; NADPH oxidase) as well as proteins involved in autolysosomal killing of bacteria and inflammasome activation (Kim et al, 2011; Shenoy et al, 2012; Haldar et al, 2015; Man et al, 2016; Feeley et al, 2017).…”
Section: Gbps In Antibacterial Defensementioning
confidence: 99%
“…Cell-autonomous defense mechanisms, which exist in MPS cells and also non-immune cells, provide a rapid antimicrobial response and evolved from the predator–prey relationship among the ancestors of current eukaryotes and prokaryotes ( 1 , 2 ). In MPS cells, cell-autonomous defenses include phagocytosis and autophagy, processes that originated in ancient eukaryotes for nutrient acquisition and reallocation.…”
Section: Introductionmentioning
confidence: 99%
“…Being haploid and amenable to molecular genetic techniques, Dictyostelium offers many advantages for identifying and characterizing host genes involved in resistance to pathogens (Bozzaro and Eichinger, 2011 ). Studies in the last decade have shown that Dictyostelium cells share with mammalian macrophages not only the basic phagocytic machinery, but also many mechanisms of innate and nutritional immunity (Bozzaro et al, 2008 , 2013a ; Cosson and Soldati, 2008 ; Soldati and Neyrolles, 2012 ; Nasser et al, 2013 ; Gaudet et al, 2016 ). Concerning transition metals, Dictyostelium cells share with macrophages the expression of the Nramp1 iron transporter in the phagolysosome, which is essential for proton-driven iron efflux from the phagosome, thus potentially starving bacteria for iron and manganese (Forbes and Gros, 2003 ; Courville et al, 2006 ; Peracino et al, 2006 ; Buracco et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%